An evaluation of urban regeneration: the effectiveness of a retail-led project in Lisbon - Guimarães, Pedro (2018)
To overcome the decline of the vitality and viability of town centres across several Western European cities, urban regeneration projects have been implemented. Despite their dissemination, there are shortcomings regarding the evaluation of the impacts produced by such projects. We aim to contribute to the existing literature on the subject by undertaking an evaluation of a retail-led urban regeneration project that was implemented in Lisbon’s historic centre. We conclude that although there were significant outputs, the project was not effective and did not manage to improve the viability of the area as an important commercial area of Lisbon.